(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. The development of new materials based on azomethine-containing derivatives makes it possible to create highly efficient optical switches, optical waveguides, and photoresists. Polymeric materials with chromophore fragments allow for a reduction in response time and an improvement in the contrast of liquid crystal displays, and are used for optical data storage. Methods. 1H NMR spectra (400 MHz) of all compounds were recorded on a Varian Mercury 400 spectrometer in dimethyl sulfoxide (DMSO-d6) and deuterochloroform (CDCl₃) relative to tetramethylsilane. Optical absorption spectra of the obtained compounds were recorded on a Perkin-Elmer UV/VIS Lambda 365 spectrometer at room temperature. The kinetics of thermoinitiated radical polymerization were investigated by the dilatometric method. The thickness of holographic media samples was measured using an MII-4 interference microscope. Results. Quinolin-4-ylmethylene-aminophenols were prepared through a one-step condensation reaction of 4-aminophenols with quinoline-4-carbaldehydes. The corresponding methacrylates were subsequently homopolymerized and copolymerized with the methyl methacrylate by free-radical polymerization method. It was established that the synthesized monomers polymerize at a higher rate than methyl methacrylate, as the chain termination rate decreases due to steric hindrance. The copolymers composition (molar ratio of monomer units in the respective copolymers) was determined by 1H NMR spectroscopy, and it was found that the calculated compositions were close to the initial monomer ratios. Based on the synthesized azomethine polymers, films for holographic recording were created by applying solutions of the azomethine polymers in 1,2-dichloroethane onto glass substrate. Conclusions. Experimental results obtained during the thermoinitiated radical polymerization of the synthesized monomers confirm their ability for active homopolymerization. Investigations of the absorption spectra of the synthesized compounds demonstrate individual photosensitivity within the corresponding spectral range.